Alison McCarthy. Interview with Mr. Anatoliy Kubrik, the parishioner of the Ukrainian Orthodox Church of the Holy Ascension of Maplewood town, New Jersey, USA - McCarthy, Alison (Young Scholars Grinchenko – Seton International Journal, 2021)
Alison McCarthy. Interview with Mr. Anatoliy Kubrik, the parishioner of the Ukrainian Orthodox Church of the Holy Ascension of Maplewood town, New Jersey, USA